Urban and rural dietary patterns: are there differences? The results of the ESSE-RF epidemiological study - N. S. Karamnova; S. A. Shalnova; V. I. Tarasov; Yu. A. Balanova; A. E. Imaeva; G. A. Muromtseva; A. V. Kapustina; S. E. Evstifeeva; O. M. Drapkina (Кардиоваскулярная терапия и профилактика, 2019)
The higher prevalence of alimentary-dependent risk factors for chronic non-communicable diseases in the Russian Federation among rural residents suggests that there are differences in the diets of city and village residents.Aim. To examine the diet differences of city and village adults.Material and methods. The analysis included representative samples from male and female population aged 25-64 years (n=21923, of which 8383 and 13550 are men and women, respectively) from 13 regions of the Russian Federation. The diet features were assessed by the frequency of consumption of themain food groups and individual eating habits: salting, the use of animal fats in cooking.Results. Rural men 18% more often than urban daily consumed meat sausages, 13% — salting and marinades and less often included in the diet meat (23%), fresh vegetables and fruits (28%), “milk, kefir, yogurt” (12%), sour cream (17%), quark (23%) and cheese (14%). Rural women less often consumed meat (19%), dairy products (18%), including cottage cheese (25%) and cheese (26%), but more often — salting (34%) and beans (10%). Rural women more often salt already prepared food — the odds ratio (OR) =1,32; 95% confidence interval (CI) 1,03-1,70 (X2=4,81, p=0,0282). Excess sugar intake among rural men was more common — OR=1,23; 95% CI 1,10-1,37 (X2=13,06, p>0,0001). The women of the village more often added butter to the dishes (sandwich, porridge, mashed potatoes, etc.) than the urban ones — OR=1,14; 95% CI 1,03-1,25 (X2=6,90, p=0,0086), in contrast to men, for whom the consumption of butter did not differ. In general, excess consumption of salt and sugar in the diet of village men was more common than among city men — OR=1,26; 95% CI 1,13-1,42 (X2=15,95, p>0,0001), in contrast to women, among whom no such differences were found (X2=3,02, p=0,0821). The diet, characterized by excessive consumption of salt, sugar and insufficient consumption of vegetables and fruits, was more often present among rural men — OR=1,30; 95% CI 1,12-1,53 (X2=10,92, p=0,0009). In urban and rural women, differences in the frequency of such diet were not found.Conclusion. The urban dietary pattern is characterized by higher consumption of meat, dairy products, vegetables and fruits, while in the rural model, the consumption of beans, salting, sugar and butter is higher.Participants of the ESSE-RF study: Moscow: Zhernakova Yu. V., Boytsov S. A., Saint-Petersburg: RotarO. P., Vladivostok: Kulakova N. V., Nevzorova V. A., Vladikavkaz: Astakhova Z. T., Vologda: Shabunova A. A., Volgograd: Nedogoda S. V., Voronezh: Chernykh T. M., Ivanovo: Belova O. A., Kemerovo: Artamonova G.V., IndukayevaE. V., Krasnoyarsk: Grinshtein Yu. I., Petrova M. M., Orenburg: Libis R. A., Samara: Duplyakov D. V., Tomsk: Trubacheva I. A., Kaveshnikov V. S., Serebryakova V. N., Tyumen: Efanov A. Yu., Medvedeva I. V., Shalaev S. V.